Employee Motivation and Job Performance of Registry Staff of Universities in Nigeria - Dada, Rcheal Olufunmilola (Archives of Business Research, 2025)
It has been observed that registry staff of universities in Nigeria have a lot of challenges in proper keeping and maintenance of students and staff records. Previous studies had been carried out on employees’ motivation and job performance in business organizations while there is dearth of literature on this area of study in higher educational institutions. This study therefore, reviewed the activities of registry staff in higher institutions of learning with respect to the employee motivation and job performance of registry staff in universities using Ogun State as case study. Survey research design was adopted for the study. The population of the study comprised of 1311 registry staff of universities in Ogun State and the sample size was determined firstly by purposive selection of five (5) universities based on years of establishment and population, which gave a target samples total number of 1021. Taro Yamane sample size computation formula was applied for appropriate selection of 399 out of 1021 sample size of registry staff. Data were collected with a validated questionnaire. The Cronbach’s alpha reliability coefficients for each of the constructs ranged from 0.70 to 0.91. The overall response rate of 0.88 was obtained. The collected copies of the questionnaire were analysed, using multiple regression analysis at 0.05 level of significance. Findings revealed that employee motivation was a significant predictor of job performance (β =0.153, p<0.05) therefore employee motivation has a significant influenced on job performance of registry staff (R2 = 0.106). The study concluded that employee motivation influenced the job performance of registry staff in universities in Ogun State, Nigeria. The study recommended that the university management ensure conducive environment for employee, make sure staff are paid well and have a robust reward package to retain and motivate staff.